Studi Persebaran dan Pemanfaatan Gayam [Inocarpus fagifer (Parkinson ex Zollinger) Fosberg] di Daerah Istimewa Yogyakarta - Albert Husein Wawo; Ninik Setyowati; Ning Wikan Utami (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
Study on ‘Distribution and Utilization of gayam [Inocarpus fagifer (Parkinson ex Zollinger) Fosberg] on several locations in Special Territory of Yogyakarta (DIY)’ was carried out from 15 until 20 September 2010. The method of this study was Purposive Random sampling and interview with local communities. The results showed that the DIY provincy was location of natural distribution of gayam. The population of gayam from each location is different, depend on soil condition and communities activities. The communities in Bantul, Sleman and Kulon Progo regencies have conserved gayam, with maintenanced gayam seedling which grew under gayam tree. Gayam grow well in sandy loam soil and silty loam soil with pH from acid till neutral. Generally this plant grow in moisture soil i.e. near water resource, a long of river bank and cannal. The chemical content of gayam seed consist of 74.87% carbohydrate, 11.63% protein, and 2.15% fat. The seed from Banjar Asri, Kulon Progo have the highest of carbohydrat (77.70%) from fresh fruit. Gayam is multipurpuse plant i.e. food, fodder, fuel wood, erosion control, herbal pesticides, and habitat for bird and bet.